ADOPSI PETANI TERHADAP INOVASI ALAT PERTANIAN MODERN PADI SAWAH DI KELURAHAN WOLOAN DUA KECAMATAN TOMOHON BARAT KOTA TOMOHON - Christian Dries Yohanes Lensun; Juliana Ruth Mandei; Jean Fanny Junita Timban (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the level of farmer adoption of the innovation of modern farming tools of rice. The study was conducted in Woloan Dua Village, Tomohon Barat Subdistrict, Tomohon City. The study lasted for three months from the beginning of January to March 2017. Sampling of lowland rice farmers using a simple random sampling method. with a sample size of 30 farmers. The type of data used in this study is Primary and Secondary data. Primary data is data obtained by conducting direct surveys through direct interviews with respondents in this case farmers. Secondary data was obtained from the Woloan Dua Village Office and the Tomohon City Agriculture Service and the internet through Google Scholar to obtain journal articles relating to the topic of research, namely about the level of farmer adoption of modern agricultural equipment innovations. Data analysis was carried out descriptively which was presented in table form. The results showed that the level of farmer Adoption of the Innovation of modern agricultural equipment in paddy rice in Woloan Dua Village, Tomohon Barat Subdistrict, Tomohon City was relatively high, where most farmers had adopted or adopted modern farming tools of wetland rice. The high level of income and education of farmers tends to show the level of farmer adoption of the innovation of modern highland rice farming tools.*eprm*